1992
DOI: 10.1002/ange.19921040531
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselektive Komplexierung vorübergehend chiral modifizierter Liganden: enantioselektive Herstellung und Konfigurationszuordnung synthetisch wertvoller η6‐Tricarbonylchrom‐1‐tetralonderivate

Abstract: Wir berichten hier uber den sequentiellen Einbau eines 3Heund eines 4He-Atoms in ' 2 ; : ['I. Das Experiment wurde mit einem BEBE-Tandemmassenspektrometer (B magnetischer und E elektrischer Sektor)[*] realisiert. Technische Einzelheiten des Experiments mogen der die Neutralisation von [He@,C,,]'+ beschreibenden Arbeitl'] entnommen werden, da die dort angestellten Uberlegungen auch fur die hier diskutierte doppelte Penetration des C;i:-Kafigs gelten.Eine Mischung von C,, und C,, (> 90 % C6J wird in der Ionenque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…1,4‐Naphthoquinone was purified by recrystallization. 1,4‐dihydroxynaphthalene ( 2 ),19 tetralin‐1,4‐dione ( 1 ),2 ( S )‐ and ( R )‐3,3‐diphenyl‐1‐butyltetrahydro‐3 H ‐pyrrolo[1,2‐ c ][1,3,2]oxazaborole [( R )‐ 6 ], its ( S )‐antipode20, [Cr(CO) 3 (NH 3 ) 3 ]21, and [Cr(CO) 3 (tetralone)]22 were synthesized according to the cited literature procedures. 1,1,4,10,10‐Hexamethyltriethylenetetramine was filtered on Al 2 O 3 and prenyl bromide was dried over CaH 2 and distilled prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…1,4‐Naphthoquinone was purified by recrystallization. 1,4‐dihydroxynaphthalene ( 2 ),19 tetralin‐1,4‐dione ( 1 ),2 ( S )‐ and ( R )‐3,3‐diphenyl‐1‐butyltetrahydro‐3 H ‐pyrrolo[1,2‐ c ][1,3,2]oxazaborole [( R )‐ 6 ], its ( S )‐antipode20, [Cr(CO) 3 (NH 3 ) 3 ]21, and [Cr(CO) 3 (tetralone)]22 were synthesized according to the cited literature procedures. 1,1,4,10,10‐Hexamethyltriethylenetetramine was filtered on Al 2 O 3 and prenyl bromide was dried over CaH 2 and distilled prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…60 Later it was found that 65 can be resolved by HPLC not only on an analytical scale but also with amounts up to some hundred milligrams by use of a Daicel OJ column. 69 More recently, the Kündig group reported another interesting access to enantiomerically pure 65, which includes a diastereoselective complexation 70 of the enantiomerically pure THP ether of 62, which is based on some precomplexation of the oxygen atoms of the THP ether substructure. Hydrolysis gave enantiomerically pure 66, which was transformed to (6aR)-70 by a subsequent Swern oxidation.…”
Section: Benzocyclobutene Complexesmentioning
confidence: 99%
“…This strategy has been pursued by Schmalz et al, who used the so-called CBS reduction [51,52] in the synthesis of enantiomerically highly enriched tetralol complexes. [44] The case of 11 is different, however, because the compound bears an acetal moiety next to the keto function to be enantioselectively reduced. The methoxy groups would be likely to cause a reduction in enantiomeric excess, because their lone electron pairs might coordinate a chiral reduction catalyst at either one of the enantiotopic faces of the keto group.…”
Section: Introductionmentioning
confidence: 99%
“…[38] Complexation from the sterically more shielded endo face of the ligand system with predominant formation of rac-14 demonstrates an effect first reported by Schmalz with the complexation of tetralol derivatives, which has been explained in terms of precomplexation of chromium to a lone electron pair of the hydroxy substituent. [44] In order to en-hance the diastereomeric excess, Schmalz used dibutyl ether/heptane/THF (30:30:1), which is less prone to occupy coordination sites at chromium and thus facilitates the precomplexation process. When we used a 1:1 mixture of dibutyl ether and heptane with a catalytic amount of THF as solvent, we were delighted to obtain rac-14 as the only isolated diastereomer, with only traces of rac-15 being detectable by TLC.…”
Section: Introductionmentioning
confidence: 99%